Pembinaan kewirausahaan berbasis teknologi untuk mengembangkan jiwa Technopreneurship - Suhartini Suhartini; Aris Sudianto; Indra Gunawan; Baiq Andriska Candra Permana; Hamzan Ahmadi; Imam Fathurrahman; Lalu Kerta Wijaya; Muhammad Wasil; Nurhidayati Nurhidayati (Universitas Hamzanwadi, 2021)
The development of MSMEs (Micro, Small and Medium Enterprises) in Indonesia is currently very fast, as indicated by the increasing number of startups in Indonesia. The Indonesian government spends billions of rupiahs to encourage the millennial generation to become young entrepreneurs by developing startups to grow the Indonesian economy. Therefore, to support the government program, this service activity aims to understand technology-based entrepreneurial activities for students at Madrasah Aliyah Ridhlo Walidain NW, Batu Bangka, Jenggik that students' interest in entrepreneurship will increase and, they can become actors technopreneurs in the future. The participants understood the use of e-commerce to support the birth of new entrepreneurs who later could strengthen the finances and economy for home-based businesses. The method used to achieve this goal is by conducting lectures and practices using available platforms such as YouTube, Instagram, and Google Business. The results obtained from the activity are understanding the basic techniques for carrying out technology-based entrepreneurial activities. The final results show from this promotion include making it simple to use the platform by utilizing smartphone technology